(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The use of nitroglycerin in the treatment of angina pectoris began not long after its original synthesis in 1847. Since then, the discovery of nitric oxide as a biological effector and better understanding of its roles in vasodilation, cell permeability, platelet function, inflammation, and other vascular processes have advanced our knowledge of the hemodynamic (mostly mediated through vasodilation of capacitance and conductance arteries) and nonhemodynamic effects of organic nitrate therapy, via both nitric oxide–dependent and –independent mechanisms.